Non-reflecting boundary condition on ellipsoidal boundary - Barucq, H.; Dupouy St-Guirons, A. -G.; Tordeux, S. (Numerical analysis and applications, 2012)
The modeling of wave propagation problems using finite element methods usually requires the truncation of the computation domain around the scatterer of interest. Absorbing boundary conditions are classically considered in order to avoid spurious reflections. In this paper, we investigate some properties of the Dirichlet to Neumann map posed on a spheroidal boundary in the context of the Helmholtz equation.